Writing in pre-service teacher education: tradition and innovation in portuguese teaching - Emerson Pietri (Universidade Federal de Santa Catarina, 2019)
Linguistics has been a main reference for the development of renewal proposals for Portuguese teaching in Brazil since the late 1970s. Discourses on the need for renewal polemicize with pedagogical discourses characterized as traditional, which are referenced in prescriptive conceptions of language use. This work aims to know the effects of competing conceptions of language and of Portuguese language teaching on pre-service teacher education. The data were produced through enunciative processes in which writing was a device for elaboration and reflection, by student teachers and teacher educator, on conceptions of language and teaching. Data analysis evidenced the effects of traditional pedagogical discourse on the modes of interpreting knowledge produced by the language sciences. The results also point out the relevance of writing's materiality for teacher education developed dialogically.